2005
DOI: 10.2477/jccj.4.43
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dopamine D1 Receptor Agonists and Antagonists under Existing Noise Compounds by TFS-based ANN and SVM

Abstract: This paper describes classification and prediction for pharmacologically active classes of drugs under the presence of noise chemical compounds. Dopamine D1 receptor agonists (63 compounds), antagonists (169 compounds) and other drugs (696 compounds) were used for the work. Each drug molecule was characterized with Topological Fragment Spectra (TFS) reported by the authors. TFS-based artificial neural network (TFS/ANN) and support vector machine (TFS/SVM) were employed and evaluated for their classification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…SVM was successfully applied to the classification of biological activity of drugs [15] [16]. In addition, SVM deterministically classify the instance being "active" or "inactive" on the basis of the discriminant surface that was determined in advance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SVM was successfully applied to the classification of biological activity of drugs [15] [16]. In addition, SVM deterministically classify the instance being "active" or "inactive" on the basis of the discriminant surface that was determined in advance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SVM deterministically classify the instance being "active" or "inactive" on the basis of the discriminant surface that was determined in advance. In the previous studies [15][17], we investigated the classification of dopamine agonists and antagonists, in which each drug belongs to a single class. It was shown that SVM performed better than the artificial neural networks with multiple output neurons [15], and the SVM in conjunction with topological fragment spectra (TFS) descriptors, we called TFS-based SVM, could successfully learn the relationships between chemical structures of the drugs and their biological activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the present approach worked very well. In another work, 29 we investigated TFSbased machine learning using unbalanced data sets. The results suggested that training by TFS-based ANN strongly depends on the size of the data set for each class.…”
Section: Specificity (%) )mentioning
confidence: 99%
“…In a previous work, we reported that an ANN approach combined with the topological fragment spectra (TFS) allowed us to successfully classify dopamine antagonists that interact with four different types of dopamine receptors, and it could be applied to the prediction of activity for class-unknown compounds. It was also shown that SVM works for this type of problem much better. However, in those cases, each compound belonged exactly to one single class, and no multilabeled compounds were included for the data sets.…”
Section: Introductionmentioning
confidence: 99%